Using area and volume measurement via weightbearing CT to detect Lisfranc instability. Issue 11 (6th January 2021) - Bhimani, Rohan; Sornsakrin, Pongpanot; Ashkani‐Esfahani, Soheil; Lubberts, Bart; Guss, Daniel; De Cesar Netto, Cesar; Waryasz, Gregory R.; Kerkhoffs, Gino M. M. J.; DiGiovanni, Christopher W.
Abstract: Weightbearing CT (WBCT) allows evaluation of the Lisfranc joint under physiologic load. We compared the diagnostic sensitivities of one‐dimensional (1D) distance, two‐dimensional (2D) area, and three‐dimensional (3D) volumetric measurement of the injured Lisfranc joint complex (tarsometatarsal, intertarsal, and intermetatarsal) on WBCT among patients with surgically‐confirmed Lisfranc instability. The experimental group comprised of 14 patients having unilateral Lisfranc instability requiring operative fixation who underwent preoperative bilateral foot and ankle WBCT. The control group included 36 patients without foot injury who underwent similar imaging. Measurements performed on WBCT images included: (1) Lisfranc joint (medial cuneiform‐base of second metatarsal) area, (2) C1‐C2 intercuneiform area, (3) C1‐M2 distance, (4) C1‐C2 distance, (5) M1‐M2 distance, (6) first tarsometatarsal (TMT1) angular alignment, (7) second tarsometatarsal (TMT2) angular alignment, (8) TMT1 dorsal step off distance, and (9) TMT2 dorsal step‐off distance. In addition, the volume of the Lisfranc joint in the coronal and axial plane were calculated. Among patients with unilateral Lisfranc instability, all WBCT measurements were increased on the injured side as compared to the contralateral uninjured side ( p values: <.001–.008). Volumetric measurements in the coronal and axial plane had a higher sensitivity (92.3%; 91.6%, respectively) and specificity (97.7%; 96.5%, respectively) than 2D and 1D Lisfranc joint measurements, suggesting them to be the most accurate in diagnosing Lisfranc instability. The control group showed no difference in any of the measurements between the two sides. WBCT scan can effectively differentiate between stable and unstable Lisfranc injuries. Lisfranc joint volume measurements demonstrate high sensitivity and specificity, suggesting that this new assessment has high clinical implications for diagnosing subtle Lisfranc instability.